Upgrading of small sewage treatment plants for ammonia removal - case of a university campus - Nuruzzaman, Md.; Mamun, Abdullah Al; Salleh, Md. Noor (Asian Research Publishing Network, 2015)
Fourteen small sewage treatment plants (STPs) are constructed to treat the sewage generated from the International Islamic University Malaysia (IIUM) Gombak campus. These plants are required to fulfil the effluent Standard B of the revised environmental quality act of Malaysia. Effluent quality data of these plants was evaluated to check the compliance with the revised effluent quality standards set by the Department of Environment (DOE), Malaysia. Secondary data (monthly) of the STPs was analysed for this study. Performance of the STPs were evaluated in terms of ammoniacal nitrogen (AN) and biochemical oxygen demand (BOD). The statistical analyses of the data revealed that the median effluent concentration of AN from all the plants usually fails to meet the allowable concentration of 20 mg/L set for Standard B. However, all of the plants are able to meet the BOD standard of 50 mg/L. This study recommends additional aeration for extended time to reduce AN concentration from the effluents of the existing plants. Another alternate solution is to construct a centralized treatment plant, preferably a sequenced batch reactor (SBR), to provide further treatment of effluent released from the existing small plants, which are unable to meet the standard set for allowable AN concentration.